Marine Regression and Palaeoenvironments During the Holocene in the Richardson River Basin, District of Mackenzie, N.W.T. - Kerr, Daniel (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1984)
ABSTRACTA detailed stratigraphie analysis was carried out on a river-bank section of late Quaternary marine sediments in the Richardson River Basin, N.W.T. The sedimentary sequence represents a gradual shallowing of the sea in an estuarine environment, from a relatively shallow marine faciès to an intertidal environment. The withdrawal of the sea from the Richardson River Basin began prior to 10,300 years BP. Isostatic uplift caused the gradual regression of the sea to its present-day level. The marine sediments yielded 26 ostracode and 14 foraminifer species. Faunal evidence is indicative of brackish-water marginal marine conditions resulting from the dilution of nearshore marine waters by freshwater discharge from the many streams and rivers draining the basin of the Richardson River.